A single base change at exon of Wx‐A1 caused gene inactivation and starch properties modified in a wheat EMS mutant line. (7th October 2021) - Zhang, Xuteng; Karim, Hassan; Feng, Xiuqin; Lan, Jingyu; Tang, Huaping; Guzmán, Carlos; Xu, Qiang; Zhang, Yazhou; Qi, Pengfei; Deng, Mei; Ma, Jian; Wang, Jirui; et al.
Abstract: BACKGROUND: Wheat is an essential source of starch. The GBSS or waxy genes are responsible for synthesizing amylose in cereals. The present study identified a novel Wx‐A1 null mutant line from an ethyl methanesulfonate (EMS)‐mutagenized population of common wheat cv. SM126 using sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and agarose gel analyses. RESULTS: The alignment of the Wx‐A1 gene sequences from the mutant and parental SM126 lines showed only one single nucleotide polymorphism causing the appearance of a premature stop codon and Wx‐A1 inactivation. The lack of Wx‐A1 protein resulted in decreased amylose, total starch and resistant starch. The starch morphology assessment revealed that starch from mutant seeds was more wrinkled, increasing its susceptibility to digestion. Regarding the starch thermodynamic properties, the gelatinization temperature was remarkably reduced in the mutant compared to parental line SM126. The digestibility of native, gelatinized, and retrograded starches was analyzed for mutant M4‐627 and the parental SM126 line. In the M4‐627 line, rapidly digestible starch contents were increased, whereas resistant starch was decreased in the three types of starch. CONCLUSION: Waxy protein is essential for starch synthesis. The thermodynamic characteristics were decreased in the Wx‐A1 mutant line. The digestibility properties of starch were also affected. Therefore, the partial waxy mutant M3‐627 might play a significant role in food improvement. Furthermore, it might also be used to produce high‐quality noodles. © 2021 Society of Chemical Industry.